Near-room-temperature magnetocaloric properties of La1−xSrxMnO3 (x = 0.11, 0.17, and 0.19) nanoparticles. (24th August 2018) - Dahal, Bishnu R; Schroeder, Kyle; Allyn, Megan M; Tackett, Ronald J; Huh, Yung; Kharel, Parashu
Abstract: The growth of chemically stable magnetic materials showing a magnetic transition near room temperature with a strong magnetocaloric effect is important for the development of room-temperature magnetic refrigeration technology. Single-phase nanoparticles of La1−x Srx MnO3 (x = 0.11, 0.17, and 0.19) (LSMO) materials in the rhombohedral crystal structure with particle sizes between 20 nm and 30 nm were prepared using the sol-gel method. The crystal structure, morphology, magnetic properties and magnetocaloric effect (MCE) were investigated. The ferromagnetic to paramagnetic phase transitions of these nanoparticles are of second order in nature and the transition temperatures (Tc ) lie between 284 K and 327 K. The magnetic entropy change (Δ S M ) and relative cooling power (RCP) exhibit a linear dependence on the applied magnetic field. All samples show relatively large cooling efficiency with Δ S M, max of 3.26 Jkg −1 K −1 for La0.89 Sr0.11 MnO3 at 297 K and RCP of 201 Jkg −1 for La0.81 Sr0.19 MnO3 both measured at H = 30 kOe. These results suggest that the LSMO nanoparticles have potential for room-temperature magnetic refrigeration.